Impact of autistic traits on the anxiety-linked attentional bias to negative information. (October 2022) - South, Emily; Papaelias, Sarah; Grafton, Ben; MacLeod, Colin; Maybery, Murray
Abstract: Background: Cognitive models propose that an attentional bias to negative information (ABNI) plays a key role in the aetiology and maintenance of high trait anxiety. The findings from previous research suggest that high autistic symptoms may attenuate anxiety-linked difference in ABNI. Method: This possibility was investigated by screening candidate participants (n = 871) on the Autism Spectrum Quotient and the Spielberger State-Trait Anxiety Inventory, and then recruiting four groups representing the combination of high/low autistic traits and high/low trait anxiety (n = 89), with participants completing a dot-probe task. Results: Results demonstrated a significant anxiety-linked difference in ABNI in participants high in autistic traits, but not in participants low in autistic traits. Conclusions: This pattern of findings stands in clear contradiction to the hypothesis that high levels of autistic traits attenuate anxiety-linked difference in ABNI. Highlights: Aetiology of high trait anxiety in autistic individuals is not well understood. High autistic traits may reduce anxiety-linked negative attention bias. Prior research investigating this issue has been methodologically compromised. High autistic traits did not reduce anxiety-linked negative attention bias.